Coping as a resource to allow for psychosocial adjustment in fatal disease: results from patients with amyotrophic lateral sclerosis - Finsel, Julia; Rosenbohm, Angela; Peter, Raphael S.; Bäzner, Hansjörg; Börtlein, Axel; Dempewolf, Silke; Schabet, Martin; Hecht, Martin; Kohler, Andreas; Opherk, Christian; Nägele, Andrea; Sommer, Norbert; et al. (Frontiers in Psychology, 2024)
Background: Amyotrophic Lateral Sclerosis (ALS) is a fatal disorder, which imposes severe emotional burden on patients. Appropriate coping may alleviate burden and facilitate well-being with social support known to be a successful coping strategy. The objective of this observational study was to determine the interplay of general coping traits of hope for success and fear of failure, coping behavior of social activity and patients' well-being. Methods: In this cross-sectional study, patients with ALS from a clinical-epidemiological registry in Southwestern Germany were interviewed on coping traits (achievement motivated behaviour: hope for success and fear of failure), coping behavior of social activity and psychosocial adjustment, determined with depressiveness, anxiety (both measured by Hospital Anxiety and Depression Scale [HADS]) and quality of life (Anamnestic Comparative Self-Assessment, [ACSA]). Demographics, clinical (ALS Functional Rating Scale revised version, [ALSFRS-R]) and survival data were recorded.Results: In total, N=868 patients (60.70% male, mean age: 64.70 (± 10.83) years, mean ALSFRS-R: 37.36 ± 7.07), were interviewed. Anxiety in patients was associated with high fear of failure, whereas a generally positive attitude in patients, exemplified in high hopes for success was associated with better well-being. Finally, coping behavior of social activity explained up to 65% of variance of depressiveness in patients with ALS.We hereby present evidence that well-being in ALS is not an immediate, fatalistic consequence of physical degradation but rather determined by coping traits and behavior, which may be trained to substantially increase well-being in patients with ALS.